Analisis Makna Kata Enak dan Kuchi Sebagai Polisemi (Kajian Linguistik kognitif) - Sulhiyah Sulhiyah (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2018)
As a system, language consists of several elements or levels that form a complete construction. These elements are sounds or phonemes, morphemes, words, phrases, clauses, sentences, paragraphs, and discourses. Furthermore, these elements can be studiedthrough the branches of linguistics that have been available in accordance with theseelements. This study aims to determine the classifcation of the meaning of polysemicmeaning "enak" and to investigate the classifcation of Polysemi meaning of the wordkuchi (mouth) from the point of view of cognitive linguistics. The research method usedis qualitative descriptive (descriptive research) by recording from several references. thetechnical method and data collection are carried out using the listening method and tapping technique, while the advanced technique is a note-taking technique. From the resultsof the study, it was concluded that the word tasty not only means the delicious taste ofa food that is felt by the taste buds, but also the feeling felt by all members of the bodyand feelings. The word kuchi not only has the meaning of an oral cavity, but it can beinterpreted as a good deed that is good or bad, and can also be interpreted as a job seeking activityKeywords: cognitive linguistics, fgure of speech, enak, kuchi (mouth)